Living in the environment - Miller, G. Tyler; Spoolman, Scott E. (United States: Cengage Learning, 2021)
'College textbook. From the Preface, For Instructors: We wrote this book to help you achieve three important goals: first, to explain to your students the basics of environmental science; second, to help your students use this scientific foundation to understand the environmental problems that we face and to evaluate possible solutions to them; and third, to inspire your students to make a difference in how we treat the earth on which our lives and economies depend, and thus in how we treat ourselves and our descendants'--